COVID-19 pandemic and mental health consequences: Systematic review of the current evidence - Vindegaard, Nina; Benros, Michael Eriksen (Brain, behavior, and immunity, 2020)
•COVID-19 patients displayed high levels of PTSS and increased levels of depression.•Patients with preexisting psychiatric disorders reported worsening of psychiatric symptoms.•Higher levels of psychiatric symptoms were found among health care workers.•A decrease in psychological well-being was observed in the general public.•However, well conducted large-scale studies are highly needed. During the COVID-19 pandemic general medical complications have received the most attention, whereas only few studies address the potential direct effect on mental health of SARS-CoV-2 and the neurotropic potential. Furthermore, the indirect effects of the pandemic on general mental health are of increasing concern, particularly since the SARS-CoV-1 epidemic (2002–2003) was associated with psychiatric complications. We systematically searched the database Pubmed including studies measuring psychiatric symptoms or morbidities associated with COVID-19 among infected patients and among none infected groups the latter divided in psychiatric patients, health care workers and non-health care workers. A total of 43 studies were included. Out of these, only two studies evaluated patients with confirmed COVID-19 infection, whereas 41 evaluated the indirect effect of the pandemic (2 on patients with preexisting psychiatric disorders, 20 on medical health care workers, and 19 on the general public). 18 of the studies were case-control studies/compared to norm, while 25 of the studies had no control groups. The two studies investigating COVID-19 patients found a high level of post-traumatic stress symptoms (PTSS) (96.2%) and significantly higher level of depressive symptoms (p = 0.016). Patients with preexisting psychiatric disorders reported worsening of psychiatric symptoms. Studies investigating health care workers found increased depression/depressive symptoms, anxiety, psychological distress and poor sleep quality. Studies of the general public revealed lower psychological well-being and higher scores of anxiety and depression compared to before COVID-19, while no difference when comparing these symptoms in the initial phase of the outbreak to four weeks later. A variety of factors were associated with higher risk of psychiatric symptoms and/or low psychological well-being including female gender, poor-self-related health and relatives with COVID-19. Research evaluating the direct neuropsychiatric consequences and the indirect effects on mental health is highly needed to improve treatment, mental health care planning and for preventive measures during potential subsequent pandemics.